Subverting the Mandates of Our Methods: Tensions and Considerations for Incorporating Reproductive Justice Frameworks into Psychological Science. (13th June 2020) - Avery, Lanice R.; Stanton, Alexis G.
Abstract: Psychological science has had a long history of both being in collusion with and resisting the colonial and violent nature of White supremacy in the academy. The field of psychology has culpability in creating and maintaining dominant narratives that have served to justify the dehumanization of marginalized groups, particularly in regards to the methodologies used. Meaningfully integrating reproductive justice (RJ) frameworks into psychological science can drive the development of interventions for using empiricism in the service of justice for systemically vulnerable groups. This paper examines how RJ offers psychological science methodological interventions that interrogate, expose, and challenge hegemonic discourses and policies that have functioned to disempower systemically vulnerable groups.